2016
DOI: 10.3389/fsurg.2016.00043
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Saccular Cerebral Aneurysms: A Review of Current Understanding and Future Directions

Abstract: Understanding the biology of intracranial aneurysms is a clinical quandary. How these aneurysms form, progress, and rupture is poorly understood. Evidence indicates that well-established risk factors play a critical role, along with immunologic factors, in their development and clinical outcomes. Much of the expanding knowledge of the inception, progression, and rupture of intracranial aneurysms implicates inflammation as a critical mediator of aneurysm pathogenesis. Thus, therapeutic targets exploiting this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 118 publications
(115 reference statements)
1
32
0
Order By: Relevance
“…Several inflammatory mediators synthesized and/or expressed by leukocyte, such as IL-1β, IL-6, TNF-α, TLR4, and matrix metalloproteinases, will further aggravate the local inflammatory response which is closely related to an adverse outcome 35 . Maiuri, et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several inflammatory mediators synthesized and/or expressed by leukocyte, such as IL-1β, IL-6, TNF-α, TLR4, and matrix metalloproteinases, will further aggravate the local inflammatory response which is closely related to an adverse outcome 35 . Maiuri, et al .…”
Section: Discussionmentioning
confidence: 99%
“…The MMP produced from monocytes/macrophages and smooth muscle cells plays a role in extracellular matrix degradation and vascular remodeling. Interleukin (IL) 1β, IL6, tumor necrosis factor-α, TLR4, Fas, nitric oxide, and complement have been suggested to function as key molecules in the propagation of immune responses [ 39 , 44 ]. High concentrations of cytokines and chemokines have also been detected in the human plasma associated with cerebral aneurysms [ 45 ].…”
Section: Pathophysiology Of a Cerebral Aneurysmmentioning
confidence: 99%
“…NF-κB can bind to the promoter regions of a variety of proinflammatory cytokines and immunomodulatory factors and is key player in the regulation of the expression of proinflammatory genes. After activation, NF-κB is transported into the nucleus to activate the expression of downstream target genes, which in turn induces macrophage aggregation in the aneurysm wall and the degradation of the extracellular matrix ( 20 , 21 ). The changes in indicator protein expression observed in this study demonstrated that microsurgical treatment can significantly reduce the degree of the inflammatory response and reduce the expression level of MMP-9.…”
Section: Discussionmentioning
confidence: 99%